Improving The Character of Honesty and Social Science Learning Outcomes by Using Wordwall Media - Arief Priyo Baskoro; Parji Parji (STAI MA'ARIF MAGETAN, INDONESIA, 2026)
This research aims to (1) determine the improvement of the honesty character of class IX B students of MTsN 2 Magetan by using Wordwall media, (2) determine the improvement of social studies learning outcomes of class IX B students of MTsN 2 Magetan by using Wordwall media.This study used a qualitative approach with Classroom Action Research (CAR) implemented in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The subjects of this study were 30 students of class IX B. Data collection techniques were carried out through observation, questionnaires, and learning outcome tests. Meanwhile, data analysis was carried out through data reduction, data presentation (display), and conclusion drawing/verification. The results of the study indicate that the character of honesty and learning outcomes of class IX B students of MTsN 2 Magetan in social studies learning can be improved by using Wordwall media. In cycle 1, the level of honesty of students was 76.67% in the good category and in cycle 2 it increased to 80% in the good category and 20% in the very good category. While the learning outcomes of cycle 1 were 76.67% of students who completed learning increased to 93.33% of students who completed learning. Thus, the level of honesty has reached the minimum target of 80% of students including the good category and student learning outcomes have reached the minimum target of 80%. Wordwall media is able to improve the character of honesty and social studies learning outcomes of class IX B students of MTsN 2 Magetan.